Body mass index (BMI) of tuberculosis (TB) patients at tamangapa public health center - Hasni, Hasni (CV. Paperhome Indonesia, 2025)
Background: Tuberculosis (TB) remains a significant public health concern, especially in developing countries, with malnutrition being a major risk factor for its progression. Malnutrition weakens the immune system, making individuals more susceptible to TB infections. The relationship between nutrition and TB treatment outcomes is critical, as nutritional status can influence recovery and overall treatment success. This study aims to analyze the Body Mass Index (BMI) of TB patients at the Tamangapa Health Center and its implications for disease management. Methods: This study employed a quantitative approach with a cross-sectional research design, conducted in December 2024 at the Tamangapa Health Center. The study population consisted of 99 active TB patients registered between January and April 2024, all of whom were included through total sampling. Data collection involved direct observation, weight and height measurements, and BMI calculations. Data analysis was performed using descriptive statistics to determine the frequency distribution of BMI among TB patients. Results: The study found that the majority of TB patients were male (63.6%) and elderly (47.5%). Most patients had a low BMI (57.6%), while 34.3% had a normal BMI, and 8.1% were overweight. These findings highlight the prevalence of malnutrition among TB patients, which can negatively impact their recovery process. Conclusion: Malnutrition remains a common issue among TB patients, with a significant proportion experiencing underweight conditions that can hinder treatment outcomes. Proper nutritional interventions should be integrated into TB treatment programs to improve recovery rates. Addressing nutritional deficiencies through dietary improvements and health education may enhance the effectiveness of TB management strategies.